Occurrence of Isopenicillin-N-Synthase Homologs in Bioluminescent Ctenophores and Implications for Coelenterazine Biosynthesis - Francis, Warren R.; Shaner, Nathan C.; Christianson, Lynne M.; Powers, Meghan L.; Haddock, Steven H. D. (PLOS ONE, 2015)
The biosynthesis of the luciferin coelenterazine has remained a mystery for decades. While not all organisms that use coelenterazine appear to make it themselves, it is thought that ctenophores are a likely producer. Here we analyze the transcriptome data of 24 species of ctenophores, two of which have published genomes. The natural precursors of coelenterazine have been shown to be the amino acids L-tyrosine and L-phenylalanine, with the most likely biosynthetic pathway involving cyclization and further modification of the tripeptide Phe-Tyr-Tyr (“FYY”). Therefore, we searched the ctenophore transcriptome data for genes with the short peptide “FYY” as part of their coding sequence. We recovered a group of candidate genes for coelenterazine biosynthesis in the luminous species which encode a set of highly conserved non-heme iron oxidases similar to isopenicillin-N-synthase. These genes were absent in the transcriptomes and genome of the two non-luminous species. Pairwise identities and substitution rates reveal an unusually high degree of identity even between the most unrelated species. Additionally, two related groups of non-heme iron oxidases were found across all ctenophores, including those which are non-luminous, arguing against the involvement of these two gene groups in luminescence. Important residues for iron-binding are conserved across all proteins in the three groups, suggesting this function is still present. Given the known functions of other members of this protein superfamily are involved in heterocycle formation, we consider these genes to be top candidates for laboratory characterization or gene knockouts in the investigation of coelenterazine biosynthesis.